Perlindungan Konsumen Muslim Terhadap Pemenuhan Hak Atas Informasi Halal Pada Produk Kosmetik Impor Dalam Jual Beli Online di Aplikasi Shopee - Putri Khisna Herawati; Indah Parmitasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This study focused on the lack of clarity regarding halal information on imported cosmetics offered through the Shopee application, raising concerns about muslim consumer safety. The research problems is how to protect muslim consumers’ rights to halal information in the e-commerce transaction of imported cosmetic products on the Shopee application, as well as the responsibility of business actors for the distribution of imported cosmetic products without halal labels on the Shopee application. The research method adopted normative-juridical, by using a statue approach, case approach and conceptual approach. The kinds of data used for this research are secondary data, which includes primary, secondary, and tertiary legal documents, The data fro this research are collected by literature review, and then analyzed utilizing qualitative descriptive analysis method. According to the study’s findings, muslim consumers’ rights to halal information in the e-commerce transaction of imported cosmetics is not sufficiently protected by the Consumer Protection Law, the Halal Product Guarantee Law, and the Information and Electronic Transaction Law. The responsibility of business actors to compensate is absolute for the distribution of imported cosmetics without halal labels in the e-commerce transaction on the Shopee application, which causes losses to muslim consumers.